Butterfly Hug and Positive Affirmation on Academic Stress: A Quasi-Experimental Study among Santri - Safwan Amin; Fikri Sya’bana Daulay; Dwi Utari; Alfi Syahrin; Dwi Aulia Anjani; M Fikri Jaka Pratama; Ella Suzanna (Jurnal Psikologi Terapan, 2025)
Academic stress is a common psychological issue experienced by students and santri due to high academic demands. This study aimed to examine the effectiveness of the Butterfly Hug and Positive Affirmation techniques in reducing academic stress levels. A quasi-experimental method using a Non-Randomized Pretest–Posttest Control Group Design was employed, involving an experimental group and a control group. The participants were santri who experienced academic stress, measured using a validated academic stress scale. The experimental group received an intervention consisting of education and practice of the Butterfly Hug and Positive Affirmation techniques, while the control group received no treatment. Data were analyzed using paired samples t-tests and independent samples t-tests. The results indicated a significant reduction in academic stress levels in the experimental group after the intervention (p < .001), whereas no significant change was observed in the control group. These findings suggest that the Butterfly Hug and Positive Affirmation techniques are effective psychological interventions for reducing academic stress among santri. This study highlights the practical value of implementing simple and low-cost mental health interventions in educational settings.